PENERAPAN TEKNOLOGI AUGMENTED REALITY PADA MEDIA PEMBELAJARAN SISTEM PENCERNAAN BERBASIS ANDROID - Feby Zulham Adami; Cahyani Budihartanti (JURNAL TEKNIK KOMPUTER AMIK BSI, 2016)
Abstract — Augmented reality (AR) is a type of interactivetechnology combining real and virtual objects will generate 3Dobjects that will be displayed on the screen. Augmented reality hasbeen applied has a way of working is based on detection of imageor images and so-called markers, using a smartphone's camerathen detects markers that have been printed. Augmented realitywidely used in various fields, one of which is education. In the fieldof education augmented reality is used as a medium of learning tomake it more interesting. Augmented reality technology can beapplied in human anatomy learning system is one of the digestivesystem. The use of augmented reality technology is expected todisplay the objects in the form of an organ in the human digestivevirtual 3D images made using marker. Markers are detected by acamera on android smartphone will display 3D objects digestivesystem, so that users can observe how the application form organsof the digestive system in realtime. Making an application is builtusing Unity 3D and Blender software.Intisari — Augmented reality (AR) adalah jenis teknologiinteraktif menggabungkan benda nyata dan virtual yang akanmenghasilkan objek 3D yang akan ditampilkan pada layar.Augmented reality yang telah diaplikasikan memiliki cara kerjaberdasarkan deteksi citra atau gambar dan biasa disebut marker,dengan menggunakan kamera smartphone kemudianmendeteksi marker yang telah di dicetak. Augmented realitybanyak digunakan diberbagai bidang, salah satunya bidangpendidikan. Pada bidang pendidikan augmented realitydigunakan sebagai media pembelajaran agar lebih menarik.Teknologi augmented reality ini dapat diterapkan dalam sistempembelajaran anatomi manusia salah satunya adalah sistempencernaan. Penggunaan teknologi augmented reality diharapkanbisa menampilkan objek berupa organ dalam pencernaanmanusia secara virtual 3D dengan menggunakan gambar yangdijadikan marker. Marker yang dideteksi oleh kamera padasmartphone android akan menampilkan objek 3D sistempencernaan, sehingga pengguna aplikasi dapat mengamatibagaimana bentuk organ-organ sistem pencernaan secararealtime. Pembuatan aplikasi ini dibangun menggunakansoftware Unity 3D dan Blender.Kata kunci — Augmented reality, Blender, digestion, 3D, Unity3D, marker.